ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN PENDEKATAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL) PADA BANK SWASTA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Yanti, Gita Anjari; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine and analyze the level of bank health in private banks listed in Indonesia Stock Exchange (IDX) period 2011-2015 using RGEC method (Risk Profile, Good Corporate Governance, Earning, Capital).This research is descriptive research, data collection method used is by method of documentation. Measurement method of health level by using ratio as indicator of NPL, IER, LDR, NPM, ROA, CAR in financial report as secondary data.The results of the research were obtained that the assessment of bank soundness by the RGEC method was seen from the risk profile, good corporate governance, earnings, and capital factors in the 2014-2015 period. In 2014-2015, it was seen from the risk profile factor that it was in a very healthy condition (PK-1) with an average value of 86.67%. Judging from the factors of good corporate governance in 2014 was in a healthy condition (PK-2) with an average value of 13.99% NPM ratio, in 2015 was in a healthy condition (PK-2) with an average value of 15 NPM ratios , 69% on. Judging from the earnings factor in 2014, it was in a healthy condition (PK-2) with an average ROA ratio of 1.80%, in 2015 it was in a healthy condition (PK-2) with an average ROA ratio of 1.87 %. Judging from the capital factor in 2014 was in a very healthy condition (PK-1) with an average CAR ratio of 15.05%, in 2015 it was in very healthy condition (PK-1) with an average CAR ratio amounting to 15.77%.Keywords: Bank Health Level, RGEC Method, NPL, IER, LDR, NPM, ROA, CAR